A Novel Technique for Secure Data Retrieval - Sugunan, Sarika; Azeez, Arifa (IJRDO -Journal of Computer Science Engineering, 2015)
Mobile nodes in a hostile network are likely to suffer from intermittent network connectivity and frequent partitions. Disruption-tolerant network (DTN) technologies are becoming a productive solution that allow wireless devices to communicate with each other and access the confidential information or command reliably by exploiting external storage nodes. The most critical issues in this scenario are the enforcement of authorization policies and the policies update for secure data retrieval in wireless networks. Ciphertextpolicy attribute-based encryption (CP-ABE) is a promising cryptographic solution to the access management problems. However, the problem of applying CP-ABE in decentralized DTNs introduces several security and privacy challenges with regard to the attribute revocation, key escrow, and coordination of attributes issued from different authorities. In this work, we propose a secure data retrieval scheme using CP-AUBE for decentralized DTNs where multiple key authorities manage their multiple attributes independently. Also we enforce a group oriented attribute based encryption and also incorporate an efficient attribute and key renewal technology. The group oriented encryption is done with concept of Bucketization which produces an optimal solution. Hence the proposed mechanism demonstrates how to securely and efficiently manage the confidential data distributed in the disruptiontolerant network